PEMANFAATAN MANAJEMEN PEMASARAN SECARA ONLINE MELALUI APLIKASI INSTAGRAM PADA TOKO MADINAH KALISAT - Wardiyah, Silvi; Fatimah, Feti; Wibowo, Yohanes Gunawan (Growth, 2023)
Instagram is not just for sharing information, but also a means of communicating and interacting online to do business marketing. So this study aims to explain and analyze the use of STP (Segmenting, Targeting, Positioning) and marketing mix (Marketing mix) in online marketing through the Instagram application at the Medina Kalisat Shop. This study uses qualitative research with descriptive methods. From the results of the analysis that has been carried out, the researcher concludes that Toko Madinah has implemented STP well. The results of the analysis of the marketing mix (marketing mix), the company pays attention to the variables from the STP (Segmenting, Targeting, Positioning) of a company so that online marketing management can run smoothly. effective and efficient. Toko Madinah still has limited knowledge in marketing through Instagram so that the function of social media that they have is not optimal. Suggestions for optimizing online marketing through Instagram are by utilizing the features of Instagram videos, Live videos, Instagram stories, and shopping tags.